UPACARA MABERSIH DUKUH WARGA NYUWUNG DI DESA ABIANBASE GIANYAR - Harsananda, Hari (Institut Hindu Dharma Negeri Denpasar, 2018)
The Mabersih Dukuh ceremony is a unique ceremony carried out by Nyuwung residents in the village of Abianbase Gianyar. It is said to be unique because this ceremony is a kind of initiation that has a different form from the conventional initiation system that has been commonly carried out so far. Mabersih Dukuh ceremony can be coordinated like Pawisik, Mapekeling, Nyumbah, ngunggahang banten, ngarga tirtha, mar- eresik, prayer, mabyakala, malukat, foot cleansing process, Seda Raga and the stages of Natab Banten Suci, Makemit at the Panyuwungan Panti temple and Munggah Dukuh Pengarep ceremony. Mabersih Dukuh cer- emony has theological implications, namely the meeting of two teachings between Brahmaism and Sivaism. These two understandings go hand in hand as can be seen from the Mabersih Dukuh ceremony procession. This article describes in full how the chronology of the ceremony and the various things related to it. Through this description it is expected that there is a pattern of elaboration on the existence of unique ritual culture that is worthy of being known by the public so that they are increasingly aware of the diversity of religious cultures inherited by their ancestors. The inspiration obtained is an effort to save this tradition by the young- er generation so that the estapet of noble civilization continues to run well.